'An unusual response of dental sepsis to antibiotics: parallels with the Jarisch–Herxheimer reaction'. (15th June 2012) - Moss, Helen; Collier, Jonathan Marc; Collier, Sophie
Abstract : Spreading odontogenic infections are a common source of hospital admissions to Oral and Maxillofacial Surgery (OMFS) units. This report describes an unusual reaction to routine treatment for a spreading odontogenic infection in a healthy male with no known allergies, requiring the patient to be managed supportively in the resuscitation room. The patient deteriorated rapidly after the administration of paracetamol, intravenous fluids, steroids and antibiotics, demonstrating delusional behaviour, fever, rigors, tachycardia and hypoxia. Fever associated with sepsis can lead to confusional states, but similar symptoms have been described in the literature as a reaction to antibiotic therapy known as Jarisch–Herxheimer (J-H) reaction. This is potentially the first time a J-H like reaction has been described in the context of dental sepsis. The authors feel that the OMFS team should be aware of possible sequelae of medical therapy in patients with acute dental sepsis and be confident in their management of these complications.